Stability of a tilt-controlling axial gap self-bearing motor with single-stator - Satoshi UENO (The Japan Society of Mechanical Engineers, 2017)
This paper discusses the stability of a tilt-controlling axial gap self-bearing motor with a single stator. The motor consists of a stator and a disc rotor and is capable of controlling motor torque, axial position, and tilt angles. The stator has six coils, which are driven by separate amplifiers. By adding two types of current (a motor current, which has the same poles as the rotor, and a tilt control current, which has plus two or minus two poles of the rotor), four degrees of freedom of the rotor can be actively controlled. In this paper, the motor torque, axial force, tilt torques, and radial forces are theoretically analyzed and their control methods of them are derived. The stability of the rotor is discussed and the influence of the position of the center of gravity is shown. The experimental results confirm the analytical results, and it is shown that the stable levitation and rotation are achieved with 2-pole and 4-pole rotors.